The contribution of formal planning to decisions - Sinha, Deepak K. (Strategic Management Journal, 1990)
Abstract This paper presents results from a study of the contribution of formal strategic planning to 1087 decisions made by 129 of the Fortune 500 companies during the years 1982–86. Multivariate analysis of covariance revealed that the characteristics of decisions account for over 15 percent of the variance in data and should therefore be regarded as important determinants of the contribution planning makes to decision‐making. The planning systems studied contributed more to decisions that were considered important and risky, and also to those that were either global in nature or related to divestments.